UPAYA PENGEMBANGAN EKONOMI MASYARAKAT DENGAN PEMBUATAN SEDIAAN OBAT TRADISIONAL DI KECAMATAN TEGALREJO, KOTA YOGYAKARTA, DAERAH ISTIMEWA YOGYAKARTA - Romadhonsyah, Fitra; Amin, Azizah; Jumaryatno, Pinus; Riyanto, Riyanto; Haryanto, Yon; Karunia, Bibit Cahya; Hartanto, Hartanto; Azzami, Muhyiddin Fathan (As-Sidanah, 2025)
Jamu is one of Indonesia's traditional medicines that is widely consumed by the public. According to a national survey in 2023, nearly 50% of Indonesians use jamu for treatment or maintaining their health. Public interest in jamu has been increasing in recent years, creating more opportunities to generate new jobs. However, a major challenge is the lack of knowledge among entrepreneurs and the public about processing raw materials for jamu and developing innovative products. The purpose of this community service program is to enhance knowledge and skills in processing raw materials into innovative jamu products with high market value. The program's partners are the members of RT 15/RW 5, Tegalrejo District, Yogyakarta. A total of 52 members of RT 15/RW 5 Tegalrejo participated in this activity. The method used in this community service program is service learning, involving the UII pharmacy department and the community on the topic of traditional medicine production, including providing basic information about traditional medicine to the community and conducting preliminary tests to assess initial understanding.. It is followed by a training on making jamu products, such as instant ginger powder, beras kencur drinks, and butterfly pea flower drinks. The activity concludes with a post-test. The results show that this community service program improves understanding of traditional medicine and enhances the community's skills in producing marketable traditional medicine products, which can serve as business ideas in the traditional medicine sector.